2016
DOI: 10.1016/j.hpb.2016.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous vs. endoscopic pre-operative biliary drainage in hilar cholangiocarcinoma – a systematic review and meta-analysis

Abstract: The accepted practice is for most jaundiced HCCA patients to have preoperative drainage of the future liver remnant. EBD may be associated with more immediate procedure-related complications, although it is certainly not inferior compared to PTBD in the long term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
70
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(77 citation statements)
references
References 44 publications
1
70
0
6
Order By: Relevance
“…One previous study did show a significantly higher rate of cholangitis with SOV EBD in surgical patients, but this cohort had a median of 105 days between drainage and surgery, a time period that likely allowed for infectious complications to manifest . A meta‐analysis evaluating biliary drainage in hilar cholangiocarcinoma via percutaneous and endoscopic approaches has, similar to our study, found no significant difference in rates of cholangitis or mortality specifically in the 30 days after intervention …”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…One previous study did show a significantly higher rate of cholangitis with SOV EBD in surgical patients, but this cohort had a median of 105 days between drainage and surgery, a time period that likely allowed for infectious complications to manifest . A meta‐analysis evaluating biliary drainage in hilar cholangiocarcinoma via percutaneous and endoscopic approaches has, similar to our study, found no significant difference in rates of cholangitis or mortality specifically in the 30 days after intervention …”
Section: Discussionsupporting
confidence: 70%
“…In light of this, biliary drainage represents an important and potentially definitive modality for palliating symptoms of obstructive jaundice . In instances when biliary obstruction remains unrelieved, subsequent cholestasis and cholangitis can considerably impact morbidity . Unfortunately, stenting procedures themselves can be compromised in their therapeutic goals by introducing enteric flora into an otherwise sterile biliary tree .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, it has been demonstrated that the icteric liver exhibits reduced tolerance for I/R injury (8,9). However, the majority of cholangiocarcinoma cases coexist with OJ (10).…”
Section: Introductionmentioning
confidence: 99%